EUFEMISME DALAM TEKS DRAMA JALAN LURUS KARYA WISRAN HADI - Mulya, Jumiatul (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
This study aims to describe the form and meaning of the euphemism contained in the drama text Jalan Lurus by Wisran Hadi. This type of research is descriptive qualitative. Data obtained from drama text Jalan Lurus. The research data was collected using the refer method. This method is continued with the SBLC technique. Data collection is also supported by note taking techniques. Data analysis methods used are the method of distribution and the method of matching. The results of the analysis of the use of euphemisms in the drama text Jalan Lurus by Wisran Hadi show that euphemisms consist of words, phrases, clauses, and sentences. Based on the data that has been analyzed, the most commonly found form of euphemism is in the form of words and the smallest form of euphemism used in the drama Jalan Lurus by Wisran Hadi is in the form of sentences. The meaning of euphemism contained in the text of the drama Jalan Lurus by Wisran Hadi is connotative and affective.